DETERMINANT OF AUDIT DELAY: EMPIRICAL STUDY OF COMPANIES IN INDONESIA - Ludwina Harahap (INQUISITIVE : International Journal of Economic, 2023)
This paper examines the relationship between profitability, solvability, auditor opinion, and auditor reputation with audit delay in companies in Indonesia. This type of research is quantitative research. The data used are audited financial statements that are published by the company every year. The sampling technique uses the purposive sampling method. The results show that profitability has a significant effect on audit delay. However, we fail to find evidence that solvability, audit opinion, and auditor reputation are associated with the timeliness of the audit report. The result confirms the signaling theory that a company that has positive earnings or income will submit the financial report promptly to communicate to investors about the firm good economic conditions.